Is logistically motivated ex vivo lung perfusion a good idea? - Van De Wauwer, Caroline; van Suylen, Vincent; Zhang, Zhang L.; Verschuuren, Erik A. M.; van der Bij, Wim; Gan, C. Tji; Ubbink, Rinse; Erasmus, Michiel E. (Frontiers in Transplantation, 2022)
Ex vivo lung perfusion (EVLP) is a technique for the reconditioning and evaluation of lungs. However, the use of EVLP for logistical reasons is still under discussion. In this retrospective study, all EVLPs performed between July 2012 and October 2019 were analyzed for ventilation and perfusion data. After transplantation: primary graft dysfunction (PGD), lung function, chronic lung allograft dysfunction (CLAD) free and overall survival were analyzed. Fifty EVLPs were performed. Seventeen logistic EVLPs leading to 15 lung transplantations (LT) and 2 rejections (LR) and 33 medical EVLPs resulting in 26 lung transplantations (MT) and 7 rejections (MR). Pre-EVLP PaO2 was lower in MT versus LT (p < 0.05). Dynamic lung compliance remained stable in MT and LT but decreased in MR and LR. Plateau airway pressure started higher in MR (p < 0.05 MT versus MR at T60) and increased further in LR. After transplantation, there were no differences between MT and LT in PGD, lung function, CLAD free survival and overall survival. Next to this, the LT group was compared with a cohort group receiving standard donor lungs without EVLP (LTx). There were no significant differences between LT and LTx for PGD, CLAD free survival and overall survival. FVC was significant lower in LT versus LTx at 1 year (p = 0.005). We found that LT lungs seems to perform better than MT lungs on EVLP. In turn, outcome in the LT group was comparable to the LTx group. Lung transplantation after EVLP for logistic reasons is safe and makes transplantation timing controllable.